Harnessing AI for Faster Innovation: How AI Concept Generation Impacts Development Timelines and Market Agility - Ateeq, Karamath; Masaeid, Turki Al; Selim, Hany; Oswal, Nidhi; Alkubaisy, Amer Ayada Ayoub; Alami, Rachid; Ajdoobi, Saeed Mohamed Ghuloum Ajdoobi (Journal of Posthumanism, 2025)
This paper examines the impact of AI-driven concept generation on development cycles and market responsiveness. As organisations face pressure to innovate rapidly, AI is increasingly leveraged to accelerate product ideation, streamline prototyping, and enhance decision-making. This study explores whether AI-driven concept generation reduces time-to-market while maintaining product-market alignment. This research synthesises existing literature and industry case studies on AI applications in product management, supply chain optimisation, and business model innovation. Drawing on interdisciplinary perspectives, it critically evaluates AI’s role in automated design exploration, data-driven decision-making, and market validation. A theoretical lens grounded in organisational behaviour and technology adoption frameworks underpins the analysis. AI-driven concept generation substantially reduces development cycles by enabling rapid prototyping, data-informed ideation, and real-time customer feedback loops. AI enhances firms’ adaptability to market fluctuations by automating design exploration and improving strategic decision-making. However, the effectiveness of AI-generated concepts is contingent on data quality, human oversight, and organisational integration. While AI fosters efficiency, its benefits predominantly accrue to larger firms with robust AI infrastructure, potentially reinforcing industry concentration. This paper contributes to the discourse on AI in organisational behaviour by synthesising insights across multiple domains. It provides a nuanced understanding of AI’s role in product innovation and strategic agility, offering implications for managers, policymakers, and researchers.